Nitrogen balance in Holstein steers grazing winter oats: Effect of nitrogen fertilisation - Sánchez Chopa, Federico (2015)
The present study evaluated the effect of nitrogen (N) fertilisation of winter oats on whole-animal N balance (N intake, N excretion in urine and faeces, N retention), partition of urinary N (purine-N derivatives and urea-N) and average daily gain (ADG) in grazing steers. The experimental area was divided in two plots (10 steers/plot), and samples were obtained in two periods (one plot/period).The experimental area was divided in two plots, and each plot in 10 strips. Twenty Holstein steers (161.3 ± 7 kg of initial bodyweight) grazed, for 51 days, individual strips of fertilised (100 kg N/ha; N100) and non-fertilised (N0) winter oats during daylight (10 h/day). The daily individual grazing paddock was adjusted to offer 6 kg DM of green leaf·100 kg/BW.day. Chemical composition of the herbage and N diurnal variation were estimated by collecting three samples per paddock at 0830 hours, 1330 hours and 1830 hours, twice on each sampling period. Forage intake and in vivo digestibility were estimated by the n-alkane technique. Individual N intake was estimated using n-alkane data, the ingestive behaviour data and the diurnal variation of the chemical composition of the forage. N fertilisation increased N content [P < 0.01; N0 ≤ 11.4% crude protein (CP) vs N100 ≤ 13.9% CP] and decreased the water-soluble carbohydrate content (P < 0.01; N0 ≤ 21.1% vs N100 ≤ 16.8%) in the forage, but did not modify herbage mass or the DM content. Dry matter intake (4.72 kg DM/day), water intake (7.57 L/day) and DM digestibility (67%) were not affected by N fertilisation. However, N intake and N digestibility were higher in N100 than in N0 (20 vs 7 g N/day). Although treatments had similar faecal N excretions (average 45.4 g N/day), there was a trend to increase urinary N excretion with N intake (P ≤ 0.08; N100 ≤ 53.3 vs N0 ≤ 47.5 g N/day), a trend to increase N-allantoin excretion (P ≤ 0.11; N100 ≤ 3.18 vs N0 ≤ 2.91 g/day) and an increase in urea-N excretion (P < 0.01; N100 ≤ 30.7 vs N0 ≤ 23.8 g/day). Increasing N intake led to greater N retention (P < 0.02; N100 ≤ 37.9 vs N0 ≤ 20.9 g N/day) and ADG (P < 0.03; N100 ≤ 860 vs N0 ≤ 698 g/day). These results suggest that fertilising winter oats with 100 kg N/ha improves N retention and ADG in young steers under grazing conditions.